Research on the Content of Minerals and Heavy Metals in Some Popular Afterschool Snacks - Huan, Nguyen Xuan; Thanh Nga, Do; Ngoc Bao Tram, Le (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Nowadays, cheap snacks with stimulating flavors are popular among students. However, some snacks may contain heavy metals and minerals at levels that are harmful to long-term health. The study focused on studying the content of macrominerals, trace minerals, and heavy metals in eight snack samples collected from grocery stores near schoolzones in Hanoi. The snack samples were analyzed using ICP-OES equipment. The analysis results detected the range of four macrominerals (Mg (53-83 mg/kg), Ca (480 - 740 mg/kg), Na (224 - 350 mg/kg), and K (239 - 352 mg/kg)); six trace minerals (Se (0 - 0.04 mg/kg), Zn (4.35 - 30.09 mg/kg), Fe (15.64 - 135.67 mg/kg), Mn (2.50 - 7.92 mg/kg), Cr (0.20 - 0.89 mg/kg), and Cu (1.11 - 2.77 mg/kg)), and four heavy metals (As (0 - 0.01 mg/kg), Sn (0.03 - 0.08 mg/kg), Hg (0.03 - 0.88 mg/kg), and Pb (0.02 - 0.1 mg/kg)).